2015
DOI: 10.1515/hsz-2015-0129
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical development of a C6-ceramide NanoLiposome, a novel sphingolipid therapeutic

Abstract: Despite the therapeutic potential of sphingolipids, the ability to develop this class of compounds as active pharmaceutical ingredients has been hampered by issues of solubility and delivery. Beyond these technical hurdles, significant challenges in completing the necessary preclinical studies to support regulatory review are necessary for commercialization. This review seeks to identify the obstacles and potential solutions in the translation of a novel liposomal technology from the academic bench to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 49 publications
1
64
0
1
Order By: Relevance
“…Since the discovery of its bioactive properties over two decades ago (Dobrowsky, Kamibayashi, Mumby, & Hannun, ), there has been great interest in developing ceramide for therapeutic purposes. However, much of this focus has been on the short‐chain ceramide analogs such as C 6 ceramide, which have seen several different approaches to deliver it to cancer cells and induce apoptosis (Dhule et al, ; Kester et al, ; Kester et al, ; Shabbits & Mayer, ; Shabbits & Mayer, ; Zhai et al, ; Zou et al, ). There has been considerably less attention devoted to the longer chain ceramides in the realm of therapeutic delivery, mostly due to the difficulties associated with these ceramides in aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of its bioactive properties over two decades ago (Dobrowsky, Kamibayashi, Mumby, & Hannun, ), there has been great interest in developing ceramide for therapeutic purposes. However, much of this focus has been on the short‐chain ceramide analogs such as C 6 ceramide, which have seen several different approaches to deliver it to cancer cells and induce apoptosis (Dhule et al, ; Kester et al, ; Kester et al, ; Shabbits & Mayer, ; Shabbits & Mayer, ; Zhai et al, ; Zou et al, ). There has been considerably less attention devoted to the longer chain ceramides in the realm of therapeutic delivery, mostly due to the difficulties associated with these ceramides in aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these methods have centered around the use of the short chain C 6 ceramide, a synthetic ceramide analog which is a potent inducer of apoptosis (Zhai, Sun, Han, Jin, & Zhang, 2015). One of the more common methods of short chain ceramide delivery is liposomes, which incorporate C 6 ceramide or other short chain ceramides into constructs containing other co-factors (Kester et al, 2015;Shabbits & Mayer, 2003a;Zou et al, 2014). However, when introduced into an aqueous environment, ceramide rapidly releases from the liposomes, limiting their systemic delivery (Zolnik et al, 2008).…”
mentioning
confidence: 99%
“…C 6 ceramide has been utilized for the development of a novel nanoliposome formulation termed ceramide nanoliposomes (CNLs). These CNLs can deliver C 6 ceramides effectively as well as synergizing with current chemotherapeuitcs by encapsulating them within the same nanoliposomes (Adiseshaiah et al, 2013; Kester et al, 2015; Ma, Mou, Ding, Zou, & Huang, 2016; Sun, Fox, Adhikary, Kester, & Pearlman, 2008). The efficacy of these CNLs is currently being investigated in a phase 1 clinical trial in patients with solid tumors.…”
Section: Deliverable and Clinically Relevantsphingolipid-based Drugs mentioning
confidence: 99%
“…The trial found that while the C 2 and C 6 ceramides had little to no toxicity, patients yielded only a 4% response rate, shelving topical administration of short chain ceramides as a potential chemotherapeutic (Jatoi et al, 2003). However, by encapsulating a C 6 ceramide into stable nontoxic nanoliposomes, researchers found that they could increase chemotoxicity as compared to free ceramide alone in in vivo models (Kester et al, 2015; Sun et al, 2008). These CNLs entered a phase I study beginning in 2017 for patients with advanced solid tumors at the University of Maryland, the University of Virginia, and the Medical University of South Carolina (Clinical trial #: NCT02834611) (ClinicalTrials.gov).…”
Section: Deliverable and Clinically Relevantsphingolipid-based Drugs mentioning
confidence: 99%
“…Nanoliposomal C6-ceramide has been investigated as a single agent and in combinatorial therapies (46), and recent work discusses preclinical development of C6-ceramide nanoliposomes (47). Of note, alterations in sphingolipid metabolism may play a crucial role in the regulation of cancer glycolytic capacity (48).…”
Section: Cellular Metabolism Of C6-ceramide and The Impact Of Tamoxifenmentioning
confidence: 99%